The association between the gut microbiome and antituberculosis drug-induced liver injury - Pei, Shengfei; Yang, Li; Gao, Huixia; Liu, Yuzhen; Lu, Jianhua; Dai, Er hei; Meng, Chunyan; Feng, Fumin; Wang, Yuling (Frontiers in Pharmacology, 2025)
BackgroundThis study aimed to explore the distinct characteristics of the gut microbiota in tuberculosis (TB) patients who experienced liver injury following anti-TB treatment compared with those who did not.MethodWe employed a nested case-control study design, recruiting newly diagnosed pulmonary TB patients at Tangshan Infectious Disease Hospital. Participants were categorized into the Antituberculosis Drug-Induced Liver Injury (ADLI) group and the Non-ADLI group based on the occurrence of liver injury after treatment. Both groups received identical anti-TB regimens. Stool samples were collected from patients who developed liver injury within 2–3 weeks of starting treatment, alongside matched controls during the same timeframe. The samples underwent 16S rDNA sequencing, and clinical data and blood samples were also collected for further analysis. At the same time, we constructed mouse models to explore the effects of different anti-tuberculosis drugs on gut microbiota.ResultsFollowing anti-TB treatment, we observed a decrease in microbial diversity and significant structural changes in the gut microbiota of TB patients (P < 0.05). At T1, the Non_ADLI_T1 group presented relatively high levels of Phascolarctobacterium, Anaerofustis and Mailhella. In contrast, the ADLI_ T1 group presented elevated levels of Bacteroides, Veillonella, Clavibacter, Corynebacterium, Anaerococcus, Gardnerella, Peptostreptococcus and Lautropia. At T2, the ADLI_T2 group presented increased levels of Enterococcus, Faecalibacterium, unclassified_f__Burkholderiaceae, Cardiobacterium, Ruminococcus_gnavus_group and Tyzzerella_4 than did the Non_ADLI_T2 group. Additionally, the ADLI_T2 group presented decreased levels of Prevotella_9, Akkermansia, Erysipelotrichaceae_UCG-003, Rubrobacter and norank_f__Desulfovibrionaceae than did the Non_ADLI_T2 group. In animal experiments, similar changes to those in the human population were observed in the mouse model compared to the control group. Any single anti-tuberculosis drug or two-drug combination or three-drug combination can cause dysbiosis of the mouse gut microbiota. The signature genera between groups are different and related to the type of anti-tuberculosis drug.ConclusionAnti-tuberculosis treatment induces dysbiosis in the gut microbiota of TB patients. Notably, there are significant differences in microbiota characteristics between TB patients with and without liver injury at both onset and during treatment. There are some differences in the characteristics of bacterial flora in liver injury caused by different drugs.